Plank Sampah, Goro, dan Tanaman TOGA Aksi Nyata dalam Menjaga Kebersihan dan KelestarianLingkungan - M. Gilang Mulya Putra; Malta Nelisa; Imratul Husna; Hamila Zakiyatu Sholeha; Muhammad Hidayat (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
The community service program titled "Educational Signage, CommunalWork (Gotong Royong), and TOGA Plants" was conducted as part of theCommunity Service Program (KKN) to foster public awareness regardingenvironmental cleanliness and sustainability. This program was motivatedby issues regarding suboptimal waste management and the lack ofproductive land utilization in the area. The implementation methodemployed a participatory approach, actively involving village residents as partners in three main activities: (1) installing educational signage; (2) conducting communal work (Gotong Royong) for cleaning and socialstrengthening; and (3) planting Family Medicinal Plants (TOGA). The results demonstrated a positive community response, evidenced bybehavioral changes such as increased discipline in waste disposal, activeparticipation in communal activities, and enthusiasm for cultivatingmedicinal plants. This program concludes that an educational andapplicative approach is effective in shaping environmental awareness andencouraging sustainable family health independence.